Effect of Multicomponent Training on Blood Pressure, Nitric Oxide, Redox Status, and Physical Fitness in Older Adult Women: Influence of Endothelial Nitric Oxide Synthase (NOS3) Haplotypes - Trape, Atila Alexandre; Silva Lizzi, Elisangela Aparecida da; Porto Goncalves, Thiago Correa; Lima Rodrigues, Jhennyfer Aline; Tavares, Simone Sakagute; Lacchini, Riccardo; Pinheiro, Lucas Cezar; Ferreira, Graziele Cristina; Tanus-Santos, Jose Eduardo; Ovidio, Paula Payao; Jordao, Alceu Afonso; Jacomini, Andre Mourao [UNESP]; et al. (Hindawi Ltd, 2017)
The purpose of this study was to verify the influence of the genotype or haplotype (interaction) of the NOS3 polymorphisms [-786T>C, 894G>T (Glu298Asp), and intron 4b/a] on the response to multicomponent training (various capacities and motor skills) on blood pressure (BP), nitrite concentration, redox status, and physical fitness in older adult women. The sample consisted of 52 participants, who underwent body mass index and BP assessments. Physical fitness was evaluated by six-minute walk, elbow flexion, and sit and stand up tests. Plasma/blood samples were used to evaluate redox status, nitrite concentration, and genotyping. Associations were observed between isolated polymorphisms and the response of decreased systolic and diastolic BP and increased nitrite concentration and antioxidant activity. In the haplotype analysis, the group composed of ancestral alleles (H1) was the only one to present improvement in all variables studied (decrease in systolic and diastolic BP, improvement in nitrite concentration, redox status, and physical fitness), while the group composed of variant alleles (H8) only demonstrated improvement in some variables of redox status and physical fitness. These findings suggest that NOS3 polymorphisms and physical training are important interacting variables to consider in evaluating redox status, nitric oxide availability and production, and BP control.